Government Officers Perception And Awareness On Online Banking - Johar, Azlan (2007)
This study has found for distinct cluster groups among government officers namely, the IT evaders, the internet surfers, the pro it users and the work oriented users. The analysis reveals that those government officers who are more inclined toward the use of information technology tend to be early adopters and have positive and lower inhibition of online banking. Hence, the young officers have less resistance toward the implementation of online banking, as they are friendly toward using information technology products.